1997
DOI: 10.1001/archneur.1997.00550170097020
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Depression in Parkinson Disease

Abstract: Most of the observations of this study favor the hypothesis that depression in PD is a primary consequence of brain dysfunction. Situational factors may, however, also contribute to mood changes in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
1
9

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 27 publications
6
110
1
9
Order By: Relevance
“…We found that although these two variables were associated with depression in univariate analyses, in the multivariate logistic regression model they were only associated with the occurrence of co-morbid psychosis and depression. If true, this suggests that previous research reporting an association between depression and both greater cognitive impairment [9] and higher levodopa doses [11] may have been confounded by the cooccurrence of psychotic symptoms. It also under-scores the importance of accounting for psychiatric and cognitive co-morbidity when determining the correlates of psychiatric disorders in PD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We found that although these two variables were associated with depression in univariate analyses, in the multivariate logistic regression model they were only associated with the occurrence of co-morbid psychosis and depression. If true, this suggests that previous research reporting an association between depression and both greater cognitive impairment [9] and higher levodopa doses [11] may have been confounded by the cooccurrence of psychotic symptoms. It also under-scores the importance of accounting for psychiatric and cognitive co-morbidity when determining the correlates of psychiatric disorders in PD.…”
Section: Discussionmentioning
confidence: 96%
“…If so, this may be due to common risk factors, including increasing age [6,8], greater cognitive impairment [4,9], and greater PD severity [6,9]. Other purported risk factors for individual disorders include exposure to most dopaminergic therapies (psychosis) [10], and female sex, predominantly right-sided motor symptoms, and treatment with higher levodopa doses (depression) [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…If there was a bias in sample selection, with a predominance of patients presenting with the rigid-akinetic form of pd or with motor complications, the study could be more prone to detect an association between motor signs and depression. In view of our current knowledge about depression in pd, it would be more suitable to regard it as a complex and multifactorial problem that also includes situational and psychological factors taking part in the mechanisms that can elicit mood changes in the patients 30 . Appropriate studies are needed to address this controversial matter.…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset PD may be a risk factor for depression [27] while research regarding the relationship between PD severity and depression has yielded mixed results [27,28,29]. Depression in PD (dPD) may precede the onset of motor symptoms [30], is often under-detected by medical professionals [31], and warrants significant attention from clinicians as it is related to a faster progression of physical symptoms, greater cognitive decline, poorer quality of life, increased caregiver burden, and decreased ability to care for oneself [32,33,34,35,36].…”
Section: Depression and Parkinson's Diseasementioning
confidence: 99%